Analysis of the law and practice governing letter of credit : Case study of selected institutions in Ilala Dar es salaam - Otieno, Magreth (Mzumbe Unversity, 2024)
Dissertation submitted in partial fulfillment of the requirements for award of the Masters Degree in Commercial Law (LL.M) of Mzumbe University.